2015
DOI: 10.1002/lary.25234
|View full text |Cite
|
Sign up to set email alerts
|

Is it necessary to retain the tensor tympani tendon in tympanoplasty?

Abstract: 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This manipulation may have led to poor performance in the FTTC group at 250 Hz. The tensor tympani tendon cut did not affect hearing at 0.5 Hz-4 kHz after tympanoplasty, 15 but tensor tympani tendon contraction is related to low-frequency hearing loss. 16 In addition, barred cartilage, which might result in decreased tension of drum, was placed under the malleus, which may be responsible for the poor performance at 4000 Hz in the FTTC group in their study.…”
Section: Discussionmentioning
confidence: 84%
“…This manipulation may have led to poor performance in the FTTC group at 250 Hz. The tensor tympani tendon cut did not affect hearing at 0.5 Hz-4 kHz after tympanoplasty, 15 but tensor tympani tendon contraction is related to low-frequency hearing loss. 16 In addition, barred cartilage, which might result in decreased tension of drum, was placed under the malleus, which may be responsible for the poor performance at 4000 Hz in the FTTC group in their study.…”
Section: Discussionmentioning
confidence: 84%
“…According to Todd [ 5 ], orientation of manubrium is inexplicably widely variable. Deng et al [ 6 ] have concluded that the section of the tensor tympani muscle tendon in canal wall-down tympanoplasty with ossiculoplasty had no statistically significant influence on sound transmission and can be a safe maneuver in middle ear surgery.…”
Section: Discussionmentioning
confidence: 99%